Malnutrition, A Global Problem: Critical Analysis - Awwal, AMM Anisul; Bhuiyan, Md Aminul Haque; Ara, Shahin; Begum, Khaleda; Nahar, Lutfun (Bangladesh Journal of Nutrition, 2010)
Bangladesh Journal of Nutrition Vol.17 2004 p.19-28